2022
DOI: 10.3389/fcimb.2022.877525
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma marginale Infection of Dermacentor andersoni Primary Midgut Cell Culture Is Dependent on Fucosylated Glycans

Abstract: Tick midgut is the primary infection site required by tick-borne pathogens to initiate their development for transmission. Despite the biological significance of this organ, cell cultures derived exclusively from tick midgut tissues are unavailable and protocols for generating primary midgut cell cultures have not been described. To study the mechanism of Anaplasma marginale-tick cell interactions, we successfully developed an in vitro Dermacentor andersoni primary midgut cell culture system. Midgut cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Moreover, α-1,3-fucosyltransferase has been demonstrated to significantly enhance the susceptibility of D . andersoni midgut cells to Anaplasma marginale infection in vitro [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, α-1,3-fucosyltransferase has been demonstrated to significantly enhance the susceptibility of D . andersoni midgut cells to Anaplasma marginale infection in vitro [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that A. phagocytophilum modulates the expression of α-1,3-fucosyltransferase during the acquisition phase in I. scapularis midgut and gene silencing significantly reduced the pathogen colonization of both tick midgut cells and murine mast cells in vitro [73,74]. Moreover, α-1,3-fucosyltransferase has been demonstrated to significantly enhance the susceptibility of D. andersoni midgut cells to Anaplasma marginale infection in vitro [75].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…In previous studies, fucosylation of bacterial related proteins or lipids, which LTL was conjugated, has been widely investigated in the bacterial infections. Vimonish et al [29] found that Anaplasma marginale regulated the differential expression of tick α-(1,3)-fucosyltransferases in midgut cells, indicating that the pathogen utilized core α-(1,3)-fucose of N-glycan to infect tick midgut cells. Sun et al [30] observed a Salmonella neuraminidase-associated compositional shift of macrophage glycocalyx using nano-LCchip QTOF mass cytometry technology.…”
Section: Discussionmentioning
confidence: 99%